2004
DOI: 10.1111/j.1467-7652.2004.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of starch can be manipulated by changing the expression levels of starch branching enzyme IIb in rice endosperm

Abstract: SummaryWhen the starch branching enzyme IIb ( BEIIb ) gene was introduced into a BEIIb-defective mutant, the resulting transgenic rice plants showed a wide range of BEIIb activity and the fine structure of their amylopectins showed considerable variation despite having the two other BE isoforms, BEI and BEIIa, in their endosperm at the same levels as in the wild-type.The properties of the starch granules, such as their gelatinization behaviour, morphology and X-ray diffraction pattern, also changed dramaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(160 citation statements)
references
References 38 publications
5
155
0
Order By: Relevance
“…When GBE is incubated with amylose, the resulting glucan products resemble glycogen with respect to chain distribution (13), compatible with the irregular branching model of Hizukuri (31). Overexpression of SBEIIb in an SBEIIb-deficient mutant of rice produced a disorganized, highly branched hydrosoluble polyglucan (56), highlighting the importance of coordination and balance between SBE and SS activities in the plastid (see "Regulation of SBEs by Protein Phosphorylation" section). Amylopectin defines the structure of the starch granule, and granule architecture is remarkably conserved in the plant kingdom (32).…”
Section: Tablementioning
confidence: 59%
“…When GBE is incubated with amylose, the resulting glucan products resemble glycogen with respect to chain distribution (13), compatible with the irregular branching model of Hizukuri (31). Overexpression of SBEIIb in an SBEIIb-deficient mutant of rice produced a disorganized, highly branched hydrosoluble polyglucan (56), highlighting the importance of coordination and balance between SBE and SS activities in the plastid (see "Regulation of SBEs by Protein Phosphorylation" section). Amylopectin defines the structure of the starch granule, and granule architecture is remarkably conserved in the plant kingdom (32).…”
Section: Tablementioning
confidence: 59%
“…The 2.9 kb mRNA band previously reported to be the normal mRNA of the OsSSI gene (Tanaka et al, 2004) was detected in wild-type and 1/1 lines, and the intensity of the band decreased gradually in the order i42/2 . i2-22/2 .…”
Section: Production Of Ssi-deficient Mutant Linesmentioning
confidence: 87%
“…Butardo et al (2011) reported that amylose content and amylopectin long chains (DP $ 36) were promoted more markedly but amylopectin short chains decreased more significantly in transgenic lines with more pronounced decrease of SBEIIb. Tanaka et al (2004) further detected that SBEIIb dosage was positively related to amylopectin short chains and negatively related to amylopectin long chains. Therefore, the question about whether the different molecular structures in TRS heterogeneous starch granules originated from the different dosages of the three SBE isoforms was raised.…”
Section: Dynamic Deposition Of Amylopectin Biosynthetic Enzymes In Thmentioning
confidence: 98%